Linguistic pluralism in the novel The "Corrupt City" )A Level Approach in Arab Fiction Models) - العرب منار; يوسف حامد جابر (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study seeks to investigate the language of the novel "The Corrupt City"; On the two sides of narration and dialogue, and referring to the ability of the Arab novelist to employ and adapt his language to fuse the form with the content, so that the language serves the meaning and expresses it The study tried to distinguish between language levels, and provide justifications and negatives in the use of each level. The literary work, but was able to support the work with realism and conformity with reality, and the novel is directed to the general readers who can read the text without difficulty because it approaches their cultural and social levels. In this research, we have studied the study of linguistic hybridization, which is a system of unifying languages, transferring the words of others into the words of the narrator-speaker, and stylization, which is the mixing of two styles within one speech style. We have presented applied examples of these definitions to support and empower them in the mind of the reader. The research showed the role of linguistic pluralism in the semantic structure of the novel The Corrupt City. Because it is the new novel that expresses a concern that contemporary human thought has long suffered from in its rupture, misery, and futility.